2006
DOI: 10.1161/01.str.0000206459.73897.a3
|View full text |Cite
|
Sign up to set email alerts
|

Endosaccular Treatment of Intracranial Aneurysms Using Matrix Coils

Abstract: Background and Purpose-The authors report their experience using Matrix coils in the treatment of cerebral aneurysms. Methods-The outcomes of 72 consecutive patients (76 aneurysms) who underwent coiling using Matrix coils at our institution were retrospectively analyzed. Results-Seventy-four aneurysms in 70 patients were coiled using Matrix coils (ranging 3% to 100% by coil length; mean 68.8%). Two patients underwent regular platinum coil embolization after failed Matrix coil placement. Thirty-two (42%) ruptur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
75
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 18 publications
5
75
3
Order By: Relevance
“…These coils have since been withdrawn from the market because numerous studies have suggested that aneurysms treated with these coils had unacceptably high recurrence rates. 11,15,16,25,30 It is likely that current endovascular results are, in fact, superior to those reported in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…These coils have since been withdrawn from the market because numerous studies have suggested that aneurysms treated with these coils had unacceptably high recurrence rates. 11,15,16,25,30 It is likely that current endovascular results are, in fact, superior to those reported in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…This latest publication is noteworthy because it is a very large multicenter series of patients. The results of this publication are disappointing in that they confirm previous findings, [1][2][3][4][5][6][7][8] suggesting that PGLA-coated coils do not lead to a decrease in angiographic recurrence rates relative to platinum coils.…”
supporting
confidence: 61%
“…[10][11][12] Several series have evaluated PGLA-coated coils showing a similar safety compared with bare platinum coils. [10][11][12]14 However, no direct comparison between patients harboring aneurysms treated with bare platinum and PGLA-coated coils has been made regarding midterm anatomic results, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%